Nitrogen-doped carbon-coated ternary nanoneedle array material, preparation method thereof and application of nitrogen-doped carbon-coated ternary nanoneedle array material in electrolysis of hydrazine hydrate

Through nitrogen-doped carbon-coated ternary nanoneedle array material, the problems of high cost of precious metal catalysts and slow reaction kinetics of non-precious metal catalysts in the prior art are solved, efficient catalytic activity and electrode conductivity are achieved, and the efficiency of hydrazine hydrate oxidation reaction is significantly improved.

CN119776898AActive Publication Date: 2025-04-08SHANDONG NORMAL UNIV

Patent Information

Application Number
CN202510204670.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-08
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

In the prior art, the application of noble metal-based catalysts in electrocatalytic hydrazine hydrate reactions is limited by high cost and poor stability. The overpotential of non-noble metal catalysts is large and the reaction kinetics are slow, resulting in a low maximum current density, limiting their application.

Method used

The ternary nanoneedle array material coated with nitrogen-doped carbon is grown in situ on the substrate through hydrothermal reaction, and the ternary nanoneedle is coated by pyrolyzed nitrogen-doped imidazole ester skeleton to form an efficient catalyst.

Benefits of technology

The enrichment of active sites and the enhancement of intrinsic activity are achieved, the catalytic activity of the catalyst and the electrode conductivity are improved, the starting potential of the hydrazine hydrate oxidation reaction is significantly reduced, and the rate of hydrogen evolution reaction and oxygen evolution reaction is increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776898A_ABST
    Figure CN119776898A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-doped carbon-coated ternary nanoneedle array material, a preparation method thereof and application of the nitrogen-doped carbon-coated ternary nanoneedle array material in electrolysis of hydrazine hydrate, and belongs to the technical field of energy catalysis. The material comprises a substrate, a ternary nanoneedle array growing on the surface of the substrate and a nitrogen-doped carbon material loaded on the surfaces of the ternary nanoneedle array and the substrate, the ternary nanoneedle is composed of any three of iron, cobalt, copper, nickel and manganese. According to the NC-loaded ternary nanoneedle array provided by the invention, enrichment of active sites and enhancement of intrinsic activity are realized through cooperation of NC and the ternary nanoneedle array, and the conductivity of the ternary nanoneedle array can be effectively improved. For a hydrogen evolution reaction and an oxygen evolution reaction, electrons can be quickly transferred between the surface of the catalyst and a reaction intermediate, so that the reaction rate is accelerated. Meanwhile, the coating structure enables water molecules to be adsorbed and activated on the surface of the catalyst more easily by adjusting adsorption energy, so that the HzOR catalytic activity is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy catalysis, and specifically relates to a nitrogen-doped carbon-coated ternary nanoneedle array material, a preparation method thereof, and an application thereof in the electrolysis of hydrazine hydrate. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Hydrogen energy has become an ideal substitute for traditional fossil energy due to its advantages such as high energy density and cleanliness. Among the many hydrogen energy production methods, electrocatalytic water splitting is currently an ideal way to obtain hydrogen energy and alleviate the energy crisis. The oxygen evolution reaction (OER) at the anode during water electrolysis is kinetically slow, which seriously limits the overall efficiency of hydrogen production by water electrolysis. Small molecule electrooxidation reactions, such as hydrazine hydrate electrooxidation reaction (HzOR), can be more efficiently coupled with the hydrogen evolution reaction (HER) at the cathode, greatly improving the hydrogen evolution efficiency. Therefore, it is of great significance to develop low-cost and efficient small molecule electrooxidation reaction catalysts.

[0004] It is generally believed that noble metals and their alloys or compounds are active electrocatalysts for electrocatalysis of HzOR. However, the high cost and poor stability of such noble metal-based catalysts limit their application in HzOR. At present, the development of transition metal oxides, hydroxides, phosphides and selenides with high earth abundance and high activity as HzOR electrocatalysts has become a research hotspot. Although a variety of non-noble metal-based catalysts have been developed, three-dimensional transition metals such as Ni and Co have also shown good electrocatalytic activity for HzOR, even better than noble metals such as Pt, but most catalysts have large overpotentials, slow reaction kinetics, and reduced maximum current density, which still hinders their application. Therefore, the design and construction of advanced non-noble metal catalysts is still a key issue that needs to be solved in the process of promoting the practical application of direct hydrazine fuel cell technology. Summary of the invention

[0005] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide a nitrogen-doped carbon-coated ternary nanoneedle array material, a preparation method thereof, and an application in the electrolysis of hydrazine hydrate. The nitrogen-doped carbon-coated ternary nanoneedle array material provided by the present invention achieves enrichment of active sites and enhancement of intrinsic activity, thereby improving the catalytic activity of the catalyst and the electrode conductivity.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] The first aspect of the present invention provides a nitrogen-doped carbon-coated ternary nanoneedle array material, comprising a substrate, a ternary nanoneedle array grown on the surface of the substrate, and a nitrogen-doped carbon material supported on the ternary nanoneedle array and the surface of the substrate;

[0008] The ternary nanoneedles are composed of any three of iron, cobalt, copper, nickel and manganese.

[0009] In some specific embodiments of the present invention, the substrate includes but is not limited to any one of foamed cobalt, foamed nickel, foamed copper, foamed manganese and foamed iron.

[0010] In some specific embodiments of the present invention, the substrate is foamed copper, and the ternary nanoneedles are composed of iron, cobalt and copper; preferably, the molar ratio of iron to cobalt in the ternary nanoneedles is 3:7.

[0011] In some specific embodiments of the present invention, the ternary nanoneedle is composed of iron, cobalt and nickel; more preferably, the molar ratio of iron, cobalt and nickel in the ternary nanoneedle is 0.7-0.8:1:1. In some specific embodiments of the present invention, the molar ratio of iron, cobalt and nickel in the ternary nanoneedle is preferably 0.75:1:1.

[0012] In some specific embodiments of the present invention, the ternary nanoneedle is composed of copper, cobalt and nickel; more preferably, the molar ratio of copper, cobalt and nickel in the ternary nanoneedle is (0.9-1.1):(0.9-1.1):(0.9-1.1). In some specific embodiments of the present invention, the molar ratio of copper, cobalt and nickel in the ternary nanoneedle is preferably 1:1:1.

[0013] In some specific embodiments of the present invention, the ternary nanoneedle is composed of iron, cobalt and manganese; more preferably, the molar ratio of iron, cobalt and manganese in the ternary nanoneedle is (0.9-1.1):(0.9-1.1):(0.9-1.1). In some specific embodiments of the present invention, the molar ratio of iron, cobalt and manganese in the ternary nanoneedle is preferably 1:1:1.

[0014] In some specific embodiments of the present invention, the ternary nanoneedle is composed of nickel, cobalt and manganese; more preferably, the molar ratio of nickel, cobalt and manganese in the ternary nanoneedle is (0.9-1.1):(0.9-1.1):(0.9-1.1). In some specific embodiments of the present invention, the molar ratio of nickel, cobalt and manganese in the ternary nanoneedle is preferably 1:1:1.

[0015] The present invention has no special limitation on the structure of the ternary nanoneedles in the nitrogen-doped carbon-coated ternary nanoneedle array material, and the structure may be a structure well known to those skilled in the art, such as a tri-metal alloy.

[0016] In some specific embodiments of the present invention, the size of the ternary nanoneedle is 3-5 μm.

[0017] The present invention has no special limitation on the loading method of the nitrogen-doped carbon material in the nitrogen-doped carbon-coated ternary nanoneedle array material, and it can be a loading method well known to those skilled in the art, such as half-coating, full-coating, and doping.

[0018] In some specific embodiments of the present invention, the loading method is preferably full coverage.

[0019] The three metals are doped to form a ternary nanoneedle array, which is then coated with a nitrogen-doped carbon material. The ternary nanoneedle array and the nitrogen-doped carbon material synergistically achieve the enrichment of active sites and the enhancement of intrinsic activity, which can effectively improve the conductivity of the ternary nanoneedle array. For the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER), electrons can be quickly transferred between the catalyst surface and the reaction intermediates, thereby accelerating the reaction rate. At the same time, this coating structure adjusts the adsorption energy, making it easier for water molecules to adsorb and activate on the catalyst surface to promote the catalytic activity of HzOR.

[0020] The second aspect of the present invention provides a method for preparing the above-mentioned nitrogen-doped carbon-coated ternary nanoneedle array material, comprising:

[0021] The ternary nanoneedles are grown in situ on the substrate by hydrothermal reaction to obtain a ternary nanoneedle array;

[0022] The ternary nanoneedle array is immersed in a 2-methylimidazolol aqueous solution, taken out, washed, and dried to obtain a ternary nanoneedle-ZIF precursor;

[0023] The ternary nanoneedle-ZIF precursor is pyrolyzed to obtain a nitrogen-doped carbon-coated ternary nanoneedle array material.

[0024] It should be noted that the electrocatalytic performance of the nitrogen-doped carbon-coated ternary nanoneedle array material prepared by the above-mentioned preparation method provided by the present invention is better than the electrocatalytic performance of the nitrogen-doped carbon-coated ternary nanoneedle array material prepared by other methods. It should be pointed out that for ordinary technicians in this technical field, the order of the preparation process can also be adjusted, such as preparing the nitrogen-doped carbon material first, and then coating the ternary nanoneedle array. That is, those skilled in the art can make several improvements and modifications to the present invention without departing from the principle of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0025] In some specific embodiments of the present invention, the substrate is pre-treated before use;

[0026] Wherein, the pretreatment comprises the steps of ultrasonication in alcohol solution, water, acid solution and water in sequence.

[0027] It should be noted that the present invention does not impose any limitation on the ultrasonic time of the ultrasound, as long as the impurities can be fully removed. For example, when the ultrasound is performed in an alcohol solution, the ultrasonic time can be 5-10 minutes to fully remove organic matter on the surface of the substrate. When the ultrasound is performed in an acid solution, the ultrasonic time can be 5-10 minutes to fully remove the oxide layer on the surface of the substrate.

[0028] Preferably, the acid includes but is not limited to one or more of hydrochloric acid, sulfuric acid and nitric acid. When ultrasonicating in an acid solution, the concentration of the acid needs to be controlled to avoid acid etching the substrate and affecting the experimental results. Therefore, it is preferred to use a low-concentration acid solution for ultrasonication, such as a 1% dilute hydrochloric acid solution.

[0029] In some specific embodiments of the present invention, the substrate includes but is not limited to any one of foamed cobalt, foamed nickel, foamed copper, foamed manganese and foamed iron.

[0030] In some specific embodiments of the present invention, the hydrothermal reaction includes: preparing a solution containing iron ions, cobalt ions, copper ions, nickel ions and / or manganese ions, adding urea and ammonium fluoride, adding the substrate and heating at 110-130°C for 5-7h to obtain a ternary nanoneedle array.

[0031] Preferably, a solution containing iron ions and cobalt ions is prepared, urea and ammonium fluoride are added, and after adding the foam copper substrate, the solution is heated at 110-130° C. for 5-7 hours to obtain a ternary nanoneedle array; the dosage ratio of metal ions, urea and ammonium fluoride is 1-1.5mmol:280-320mg:90-95mg.

[0032] Preferably, the total amount of metal in the solution is 1-1.5 mmol, the concentration of urea is 13-17 mg / mL, and the concentration of ammonium fluoride is 4-5 mg / mL. The addition of urea and ammonium fluoride can promote the hydrothermal reaction, adjust the stability of the reaction, and be conducive to the formation of a ternary nanoneedle array.

[0033] In some specific embodiments of the present invention, the volume ratio of alcohol to water in the 2-methylimidazole alcohol aqueous solution is 0.9-1.1:0.9-1.1, preferably 1:1, and the concentration of 2-methylimidazole is 0.08-0.12 g / mL.

[0034] In some specific embodiments of the present invention, the usage ratio of the ternary nanoneedle array to the 2-methylimidazolyl alcohol aqueous solution is that one piece of the ternary nanoneedle array is placed in 20-40 mL of the 2-methylimidazolyl alcohol aqueous solution; the size of the ternary nanoneedle array is 1×(3-4) cm.

[0035] In some specific embodiments of the present invention, the pyrolysis conditions are: heating to 400-500°C at a heating rate of 4-6°C / min, and keeping warm for 1.5-2.5h. Preferably, heating to 450°C at a heating rate of 5°C / min, and keeping warm for 2h.

[0036] The third aspect of the present invention provides a use of the above-mentioned nitrogen-doped carbon-coated ternary nanoneedle array material or the nitrogen-doped carbon-coated ternary nanoneedle array material prepared by the above-mentioned preparation method as a catalyst in the electrolysis of hydrazine hydrate.

[0037] A method for electrolyzing hydrazine hydrate of the present invention is characterized in that the nitrogen-doped carbon-coated ternary nanoneedle array material or the nitrogen-doped carbon-coated ternary nanoneedle array material prepared by the above-mentioned preparation method is used as an electrocatalyst.

[0038] The beneficial effects of the present invention are:

[0039] The present invention provides a nitrogen-doped carbon-coated ternary nanoneedle array material, which can be used as a catalyst for electrocatalytic hydrazine electrooxidation reaction (HzOR). The nitrogen-doped carbon (NC) carrier derived from the zeolite imidazolate framework (ZIF) is a highly conductive porous carrier, which can not only ensure the rapid transfer of charge and reduce nitrogen accumulation, but also achieve high exposure of the anchored nanocatalyst. The present invention proposes a ternary nanoneedle array loaded with NC, and the NC and the ternary nanoneedle array synergistically achieve the enrichment of active sites and the enhancement of intrinsic activity, which can effectively improve the conductivity of the ternary nanoneedle array. For hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), electrons can be quickly transferred between the catalyst surface and the reaction intermediates, thereby accelerating the reaction rate. At the same time, this coating structure makes it easier for water molecules to be adsorbed and activated on the catalyst surface by adjusting the adsorption energy to promote the catalytic activity of HzOR.

[0040] The nitrogen-doped carbon-coated ternary nanoneedle array material provided by the present invention has abundant active sites, which can effectively adsorb and activate the reactant molecules in the electrolysis of hydrazine hydrate, and can significantly reduce the starting potential of the hydrazine hydrate oxidation reaction (HzOR). It has been verified that the starting potential can be reduced by 50-100mV compared with the uncoated nanosheet array, which makes the reaction easier to start. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0042] Figure 1XRD patterns of FeCoCu-LDH (A), FeCoCu-ZIF (B) and FeCoCu-NC (C) prepared in Example 1 of the present invention;

[0043] Figure 2 SEM images of FeCoCu-LDH (A) and FeCoCu-NC (B) prepared in Example 1 of the present invention;

[0044] Figure 3 The electrochemical performance test diagram of the materials prepared in Examples 1-6 of the present invention and Comparative Example 1;

[0045] Figure 4 This is a test diagram of the electrochemical properties of the materials prepared in Comparative Examples 2-8 of the present invention. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0047] Example 1

[0048] A method for preparing a nitrogen-doped carbon-coated ternary nanoneedle array material FeCoCu-NC comprises the following steps:

[0049] Pretreatment of copper foam: Place copper foam (1×3.7 cm) in a beaker, add ethanol, and ultrasonicate for 5 minutes to remove organic matter on the surface of copper foam. Ultrasonicate in distilled water for one minute. Then ultrasonicate in 1% dilute hydrochloric acid solution for 5 minutes to remove the oxide layer on the surface. Finally, ultrasonicate with deionized water for three times.

[0050] Hydrothermal synthesis of FeCoCu-LDH: 0.39mmol of Fe(NO3)3·9H2O and 0.91mmol of Co(NO3)2·6H2O were weighed respectively, with a total metal content of 1.3mmol, of which Fe(NO3)3·9H2O accounted for 30% and Co(NO3)2·6H2O accounted for 70%, and dissolved in 20mL of deionized water, stirred evenly at room temperature to form solution A. Then 300mg of urea and 93mg of ammonium fluoride were weighed and added to solution A, stirred evenly at room temperature to form solution B. The foamed copper was placed in the polytetrafluoroethylene liner of a 50mL high-pressure reactor, and then solution B was transferred to the liner and sealed, heated at 120℃ for 6 hours, and then cooled to room temperature to obtain a foamed copper loaded with catalyst. The foamed copper loaded with catalyst was washed three times with deionized water and ethanol, and vacuum dried at 40℃ for 12h to obtain a uniform ternary FeCoCu nanosheet array.

[0051] Preparation of FeCoCu-ZIF: 15 mL of ethanol and water were measured respectively, and a mixed solution was formed by stirring at room temperature. Then 3.28 g of 2-methylimidazole was dissolved in the mixed solution of ethanol and water. A piece of ternary FeCoCu nanosheet array (1×3.7 cm) was placed in 30 mL of 2-methylimidazole ethanol and water mixed solution. After standing for 3 hours, it was taken out and washed with methanol for 3 times, and vacuum dried at 40°C for 12 hours to obtain a ternary nanoneedle-ZIF precursor (referred to as FeCoCu-ZIF).

[0052] Preparation of FeCoCu-NC: The ternary nanoneedle-ZIF precursor FeCoCu-ZIF was heated to 450°C in a tube furnace at a heating rate of 5°C / min and kept warm for 2 hours. After naturally cooling to room temperature, the final product was taken out, the nitrogen-doped carbon-coated ternary nanoneedle array material (referred to as FeCoCu-NC).

[0053] Example 2

[0054] A method for preparing a nitrogen-doped carbon-coated ternary alloy material FeCoNi-NC comprises the following steps:

[0055] Synthesis of nitrogen-doped carbon material carrier: 4.88g phenol and 1.04g NaOH solution with a volume percentage of 20% are placed in a reactor, stirred evenly, and then 8.4g formaldehyde solution with a volume percentage of 37% is added, and the reaction temperature is 70°C for 1h. After the reaction mixture is cooled to room temperature, 0.6mol / L HCl solution is used to adjust its pH to about 7.0-7.5, rotary evaporate for 2h, add 15g anhydrous ethanol solution to obtain a 20wt% phenolic resin ethanol solution, and refrigerate for standby use. Anhydrous ethanol and deionized water are added to the reactor in a mass ratio of 3:2, 10g of the above phenolic resin ethanol solution is added at a reaction temperature of 50°C, and then 2g of dicyandiamide is added and stirred to completely dissolve. 200μL concentrated nitric acid is added to the above solution, the pH of the solution is adjusted to acidic, and then stirred for 0.5h at a temperature of 50°C and a speed of 400r / min. The stirred solution was placed in an oven at 50°C for 6 hours, and then at 100°C for 24 hours. After the sample was cooled, it was placed in a tube furnace, nitrogen was first filled into the tube furnace at room temperature for 30 minutes, and then the temperature was raised to 800°C at a rate of 3°C / min, and calcined at 800°C for 5 hours to obtain a nitrogen-doped carbon material carrier for standby use.

[0056] Synthesis of nitrogen-doped carbon-wrapped FeCoNi alloy catalyst: 1.0g of nitrogen-doped carbon material carrier was vacuum dried at 110°C for 12h to fully dehydrate, and then cooled for use. 0.33g of cobalt nitrate, 0.33g of nickel nitrate and 0.33g of iron nitrate were completely dissolved in 2mL of water by ultrasound to prepare an impregnation solution. The above impregnation solution was loaded onto the surface of the dehydrated nitrogen-doped carbon material carrier by ultrasonic vibration, and then placed in a vacuum drying oven at a temperature of 100°C for 5h. After drying, it was cooled to room temperature and ground into powder. Under nitrogen conditions, the temperature was raised to 800°C at a rate of 3°C / min in a tubular furnace, and calcined for 6h, cooled, and finally the nitrogen-doped carbon-coated ternary alloy material FeCoNi-NC was obtained.

[0057] Post-treatment: The prepared nitrogen-doped carbon-coated ternary nanoneedle array material FeCoNi-NC was ground to a particle size of 100 nm, then added to a 0.1 mol / L nitric acid solution, stirred at 60 °C for 6 h, filtered, washed with deionized water until neutral, and stored in a vacuum oven at 70 °C after drying.

[0058] Example 3

[0059] A method for preparing a nitrogen-doped carbon-coated ternary alloy material CuCoNi-NC comprises the following steps:

[0060] Synthesis of ZIF precursor: 0.25 mmol copper nitrate, 0.25 mmol cobalt nitrate and 0.25 mmol nickel nitrate were dissolved in 50 mL methanol and stirred to form a mixed solution.

[0061] Prepare dimethylimidazole methanol solution: dissolve 2 mmol of dimethylimidazole in 40 mL of methanol and stir until completely dissolved.

[0062] Mixing reaction: The above two solutions were mixed, stirred at room temperature for 4 hours, and then centrifuged. The precipitate was washed with methanol for 3 times and dried at 80° C. overnight to obtain a CuCoNi-ZIF precursor.

[0063] Carbonization treatment: The obtained CuCoNi-ZIF precursor was ground into powder. The powder was placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, and calcined at this temperature for 4 hours. After calcination, it was naturally cooled to room temperature to obtain a nitrogen-doped carbon-coated ternary alloy material (abbreviated as CuCoNi-NC).

[0064] Post-treatment: The prepared CuCoNi-NC material was soaked in an appropriate amount of dilute acid (0.1 mol / L hydrochloric acid) for 2 hours to remove possible impurities on the surface, then washed with deionized water to neutrality, and then dried at 80°C.

[0065] Example 4

[0066] A method for preparing a nitrogen-doped carbon-coated ternary alloy material FeCoMn-NC comprises the following steps:

[0067] Preparation of precursor solution: Preparation of metal salt solution: Weigh 0.25mmol of iron nitrate, 0.25mmol of cobalt nitrate and 0.25mmol of manganese nitrate respectively, dissolve in 50mL of methanol, and stir to form a mixed solution of metal salts. Weigh 2mmol of dimethylimidazole, dissolve in 40mL of methanol, and stir until completely dissolved. Mix the above two solutions and stir at room temperature for 2-4 hours to form a uniform precursor solution.

[0068] Precipitation and washing: The precursor solution is allowed to stand at room temperature to allow the metal salt and the organic ligand to fully react to form a precipitate. The precipitate is separated by centrifugation at a speed of 10,000 rpm for 15 minutes. The precipitate is washed with methanol and repeated three times to remove impurities on the surface.

[0069] Drying and grinding: The washed precipitate was dried at 80°C overnight to obtain a dry precursor powder. The dry precursor powder was ground into a fine powder with a particle size of 100 nm for subsequent carbonization treatment.

[0070] Carbonization treatment: The ground precursor powder was placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, and calcined at this temperature for 4 hours. After calcination, it was naturally cooled to room temperature to obtain FeCoMn-NC material.

[0071] Post-treatment: The prepared FeCoMn-NC material was soaked in an appropriate amount of dilute acid (0.1 mol / L hydrochloric acid) for 2 hours to remove possible impurities on the surface, then washed with deionized water to neutrality, and then dried at 80 °C.

[0072] Example 5

[0073] A method for preparing a nitrogen-doped carbon-coated ternary nanoneedle array material FeCoMn-NC comprises the following steps:

[0074] Pretreatment of manganese foam: Place manganese foam (1×3.7 cm) in a beaker, add ethanol, and ultrasonicate for 5 minutes to remove organic matter on the surface of copper foam. Ultrasonicate in distilled water for one minute, and then ultrasonicate in 1% dilute hydrochloric acid solution for 5 minutes to remove the surface oxide layer. Finally, ultrasonicate with deionized water for three times to complete the pretreatment. Then dry in a vacuum drying oven at 60°C for 12 hours.

[0075] Synthesis of NiCoMn-LDH: Dissolve 0.25mmol nickel nitrate, 0.25mmol cobalt nitrate and 0.25mmol manganese nitrate in 50mL deionized water and stir evenly to form a mixed salt solution. Weigh a certain amount of sodium hydroxide to prepare a 0.25mol / L alkaline solution. Under continuous stirring, the mixed salt solution and the alkaline solution are simultaneously added dropwise to the reaction vessel containing the pretreated foam manganese, and the dropwise addition rate is controlled to keep the solution pH at 10±0.1. After the dropwise addition is completed, continue stirring for 3h. The reaction mixture is transferred to a hydrothermal reactor and crystallized at 100°C for 6-8 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged and washed several times with deionized water and ethanol, and dried overnight at 60-80°C to obtain a NiCoMn-LDH / foam manganese composite.

[0076] Synthesis of NiCoMn-ZIF: Weigh 2 mmol of dimethylimidazole, dissolve it in 40 mL of methanol, and stir until completely dissolved to obtain a dimethylimidazole methanol solution. Add the NiCoMn-LDH / foam manganese complex obtained above to another methanol solution containing 0.25 mmol nickel nitrate, 0.25 mmol cobalt nitrate and 0.25 mmol manganese nitrate, and disperse it evenly by ultrasonication. Slowly add the dimethylimidazole methanol solution dropwise to the solution containing the NiCoMn-LDH / foam manganese complex and stir at room temperature for 24 hours. Then centrifuge, wash the precipitate with methanol 3 times, and dry it at 80°C overnight to obtain a NiCoMn-ZIF / foam manganese complex.

[0077] Carbonization treatment: The NiCoMn-ZIF / foam manganese composite was placed in a tubular furnace, heated to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, and calcined at this temperature for 4 hours. After calcination, it was naturally cooled to room temperature to obtain NiCoMn-NC.

[0078] Post-treatment: The prepared NiCoMn-NC was soaked in an appropriate amount of dilute acid (0.1 mol / L hydrochloric acid) for 2 hours to remove possible impurities on the surface, then washed with deionized water to neutrality, and then dried at 80°C.

[0079] Example 6

[0080] A method for preparing a nitrogen-doped carbon-coated ternary alloy material FeCoCu-NC, which differs from Example 3 in that nickel nitrate is replaced by iron nitrate, and the remaining steps are consistent with Example 3.

[0081] Comparative Example 1

[0082] A method for preparing a nitrogen-doped carbon-coated iron single substance material Fe-NC comprises the following steps:

[0083] Weigh 2.42 g of ferric nitrate Fe(NO3)3·9H2O as an iron source. Weigh 3.0 g of melamine as a nitrogen source and a carbon source. Weigh 1.5 g of glucose as an additional carbon source.

[0084] Dissolve the weighed ferric nitrate in 50mL of deionized water and stir on a magnetic stirrer at 300r / min for 15min until it is completely dissolved to form a transparent solution. Add melamine to the above ferric nitrate solution, adjust the stirring speed to 500r / min, and stir for 30min to mix it thoroughly. Then add glucose to the mixed solution and continue stirring for 30min to evenly disperse the three substances to form a uniform mixed solution. Transfer the resulting mixed solution to an evaporating dish and continue stirring to evaporate the solvent in an 80°C water bath until a viscous gel-like substance is formed. The stirring speed is maintained at 200r / min. Transfer the gel-like substance to an oven and dry it at 100°C for 12 hours to obtain a dry precursor powder.

[0085] The precursor powder was transferred to a porcelain boat and placed in the constant temperature zone of a tube furnace. High-purity nitrogen was introduced into the tube furnace at a flow rate of 50 mL / min, and the tube furnace was heated to 900°C at a heating rate of 5°C / min and maintained at this temperature for 3 hours to allow the precursor to fully pyrolyze. After the reaction, the power of the tube furnace was turned off, and the sample was allowed to cool naturally to room temperature in a nitrogen atmosphere to obtain a black Fe-NC material.

[0086] Comparative Example 2

[0087] A method for preparing a nitrogen-doped carbon-coated cobalt single substance material Co-NC is disclosed, which differs from Comparative Example 1 in that the iron source is replaced with a cobalt source - cobalt nitrate Co(NO3)2·6H2O.

[0088] Comparative Example 3

[0089] A method for preparing a nitrogen-doped carbon-coated cobalt single substance material Co-NC, which differs from Comparative Example 1 in that the iron source is replaced with a copper source - copper nitrate Cu(NO3)2.

[0090] Comparative Example 4

[0091] A method for preparing a nitrogen-doped carbon-coated binary nanosheet material FeCo-NC is different from Example 1 in that the foamed copper is replaced with foamed cobalt, and the remaining steps are completely consistent with those of Example 1.

[0092] Comparative Example 5

[0093] A method for preparing a nitrogen-doped carbon-coated binary nanosheet material FeCu-NC is different from Example 1 in that: cobalt nitrate is not added, and 1.3 mmol of Fe(NO3)3·9H2O is added, and the remaining steps are completely consistent with Example 1.

[0094] Comparative Example 6

[0095] A method for preparing a nitrogen-doped carbon-coated binary nanosheet material CoCu-NC is different from Example 1 in that no ferric nitrate is added, and 1.3 mmol of Co(NO3)3·6H2O is added, and the remaining steps are completely consistent with Example 1.

[0096] Comparative Example 7

[0097] A method for preparing a nitrogen-doped carbon-coated quaternary nanosheet material FeCoCuNi-NC is different from that in Example 1 in that: 0.39 mmol of Fe(NO3)3·9H2O, 0.39 mmol of Co(NO3)2·6H2O and 0.52 mmol of nickel nitrate are weighed respectively, dissolved in 20 mL of deionized water, and stirred evenly at room temperature to form a solution A; the remaining steps are exactly the same as those in Example 1.

[0098] Comparative Example 8

[0099] A method for preparing a nitrogen-doped carbon-coated quaternary nanosheet material FeCoCuMn-NC, which differs from Example 1 in that: 0.39 mmol of Fe(NO3)3·9H2O, 0.39 mmol of Co(NO3)2·6H2O and 0.52 mmol of manganese nitrate are weighed respectively, dissolved in 20 mL of deionized water, and stirred evenly at room temperature to form a solution A, and the remaining steps are exactly the same as those in Example 1.

[0100] Performance Verification

[0101] 1. Structural characterization

[0102] Figure 1 XRD patterns of FeCoCu-LDH (A), FeCoCu-ZIF (B) and FeCoCu-NC (C) prepared in Example 1.

[0103] exist Figure 1In (A), by comparing the diffraction peak position in the FeCoCu-LDH spectrum with the standard card (Cu and LDH related standard card), the peak position in the spectrum is consistent with the characteristic peak position in the LDH standard card, indicating that FeCoCu-LDH has crystal structure characteristics similar to those of standard LDH. The relative intensity of the peak is close to the relative intensity of the corresponding crystal plane in the standard structure of LDH, which further supports that FeCoCu-LDH has LDH structural characteristics. Combined with the above peak position and intensity analysis, it can be inferred that FeCoCu-LDH has a layered structure of layered double hydroxide, that is, a layered structure composed of positively charged metal hydroxide layers and interlayer anions interacting through electrostatic effects and hydrogen bonds.

[0104] exist Figure 1 In (B), the diffraction peak position of the FeCoCu-ZIF sample is compared with the ZIF67 standard card. The diffraction peak at a specific 2θ angle is consistent with the characteristic peak position of the ZIF67 standard card, indicating that FeCoCu-ZIF has similar crystal structure characteristics to ZIF67. The relative intensity of each diffraction peak in the FeCoCu-ZIF spectrum is similar to the relative intensity distribution of the corresponding crystal plane in the ZIF67 standard structure, further supporting its ZIF structural characteristics. Combined with the above analysis, the characteristic peak position and relative intensity are consistent with ZIF67, which can be inferred that FeCoCu-ZIF has a structure similar to ZIF67, that is, a metal-organic framework material with a three-dimensional porous network structure formed by metal ions (Fe, Co, Cu) and imidazole ester ligands through coordination bonds.

[0105] exist Figure 1 In (C), FeCoCu-NC is compared with the Cu 85-1326 standard card. The diffraction peak at a specific 2θ angle is consistent with the characteristic peak position of Cu in the standard card, indicating that the sample has Cu-related crystal structure characteristics. From the XRD spectrum, the peaks that appear are consistent with the characteristic peaks of metals (Fe, Co, Cu) and their compounds or carbon materials. Combined with information such as its preparation process, it can be inferred that its appearance is a ternary nanoneedle array wrapped in a nitrogen-doped carbon skeleton.

[0106] Figure 2 TEM image (A) and SEM image (B) of FeCoCu-LDH prepared in Example 1 of the present invention.

[0107] exist Figure 2 In (A), FeCoCu-LDH is a ternary nanoneedle array structure. Figure 2 In (B), FeCoCu-NC exhibits nanoscale needle-like or rod-like structures, which are intertwined to form a network-like morphology. Figure 1It can be seen that the ternary nanoneedle array is wrapped in a nitrogen-doped carbon skeleton, and the FeCoCu-NC is also in the shape of a ternary nanoneedle. FeCoCu-NC is an iron-cobalt-copper-nitrogen-doped carbon material. This needle-like / rod-like interwoven structure is conducive to increasing the specific surface area of ​​the material, which has a positive impact on applications such as electrocatalysis.

[0108] 2. Electrochemical performance test:

[0109] A CHI660 electrochemical workstation was used in 1 M KOH + 0.1 M hydrazine hydrate electrolyte, with the materials obtained in the examples and comparative examples as the working electrode, a platinum sheet as the counter electrode, and a Hg / HgO electrode as the reference electrode to construct a three-electrode system. The voltage range of the cyclic voltammetry was -0.3-1.8 V vs. RHE, the scan rate was 100 mV / s, and the LSV was tested after 10 cycles.

[0110] Figure 3 The electrochemical performance test diagram of the materials prepared in Examples 1-6 of the present invention and Comparative Example 1. Among them, under the same potential, Example 1 has the highest current density and the best catalytic performance, while Comparative Example 1 has the lowest current density and the worst catalytic performance.

[0111] Figure 4 The electrochemical performance test diagram of the materials prepared in Comparative Examples 2-8 of the present invention. Among them, the electrochemical performance of the materials prepared in Comparative Examples 2-8 is much lower than that of the materials in the embodiment. It can be seen that only the materials obtained within the scope of the present invention have excellent electrochemical performance.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nitrogen-doped carbon-coated ternary nanoneedle array material, characterized in that: The invention comprises a substrate, a ternary nanoneedle array grown on the surface of the substrate, and a nitrogen-doped carbon material loaded on the ternary nanoneedle array and the surface of the substrate; The ternary nanoneedles are composed of any three of iron, cobalt, copper, nickel and manganese.

2. The nitrogen-doped carbon-coated ternary nanoneedle array material according to claim 1, characterized in that: The substrate comprises any one of foamed cobalt, foamed nickel, foamed copper, foamed manganese and foamed iron; Preferably, the substrate is foamed copper, and the ternary nanoneedles are composed of iron, cobalt and copper; preferably, the molar ratio of iron to cobalt in the ternary nanoneedles is 3:7; Preferably, the ternary nanoneedle is composed of iron, cobalt and nickel; preferably, the molar ratio of iron, cobalt and nickel in the ternary nanoneedle is 0.7-0.8:1:1; Preferably, the ternary nanoneedle is composed of copper, cobalt and nickel; preferably, the molar ratio of copper, cobalt and nickel in the ternary nanoneedle is (0.9-1.1):(0.9-1.1):(0.9-1.1); Preferably, the ternary nanoneedle is composed of iron, cobalt and manganese; preferably, the molar ratio of iron, cobalt and manganese in the ternary nanoneedle is (0.9-1.1):(0.9-1.1):(0.9-1.1); Preferably, the ternary nanoneedle is composed of nickel, cobalt and manganese; preferably, the molar ratio of nickel, cobalt and manganese in the ternary nanoneedle is (0.9-1.1):(0.9-1.1):(0.9-1.1).

3. The nitrogen-doped carbon-coated ternary nanoneedle array material according to claim 1, characterized in that: The size of the ternary nanoneedle is 3-5 μm.

4. A method for preparing the nitrogen-doped carbon-coated ternary nanoneedle array material according to any one of claims 1 to 3, characterized in that: include: The ternary nanoneedles are grown in situ on the substrate by hydrothermal reaction to obtain a ternary nanoneedle array; The ternary nanoneedle array is immersed in a 2-methylimidazolol aqueous solution, taken out, washed, and dried to obtain a ternary nanoneedle-ZIF precursor; The ternary nanoneedle-ZIF precursor is pyrolyzed to obtain a nitrogen-doped carbon-coated ternary nanoneedle array material.

5. The preparation method according to claim 4, characterized in that: The substrate is used after being pre-treated; Wherein, the pretreatment comprises the steps of ultrasonication in alcohol solution, water, acid solution and water in sequence; Preferably, the substrate comprises any one of foamed cobalt, foamed nickel, foamed copper, foamed manganese and foamed iron.

6. The preparation method according to claim 4, characterized in that: The hydrothermal reaction comprises: preparing a solution containing iron ions, cobalt ions, copper ions, nickel ions and / or manganese ions, adding urea and ammonium fluoride, adding the solution to the substrate, heating the solution at 110-130° C. for 5-7 hours, and obtaining a ternary nanoneedle array; Preferably, a solution containing iron ions and cobalt ions is prepared, urea and ammonium fluoride are added, and after adding the foam copper substrate, the solution is heated at 110-130° C. for 5-7 hours to obtain a ternary nanoneedle array; the dosage ratio of metal ions, urea and ammonium fluoride is 1-1.5mmol:280-320mg:90-95mg.

7. The preparation method according to claim 4, characterized in that: The volume ratio of alcohol to water in the 2-methylimidazole alcohol aqueous solution is 0.9-1.1:0.9-1.1, and the concentration of 2-methylimidazole is 0.08-0.12 g / mL; The usage ratio of the ternary nanoneedle array to the 2-methylimidazolyl alcohol aqueous solution is that one piece of the ternary nanoneedle array is placed in 20-40 mL of the 2-methylimidazolyl alcohol aqueous solution; the size of the ternary nanoneedle array is 1×(3-4) cm.

8. The preparation method according to claim 4, characterized in that: The pyrolysis conditions are: heating to 400-500° C. at a heating rate of 4-6° C. / min and keeping the temperature for 1.5-2.5 hours.

9. Use of the nitrogen-doped carbon-coated ternary nanoneedle array material according to any one of claims 1 to 3 or the nitrogen-doped carbon-coated ternary nanoneedle array material prepared by the preparation method according to any one of claims 4 to 8 as a catalyst in the electrolysis of hydrazine hydrate.

10. A method for electrolyzing hydrazine hydrate, characterized in that: The nitrogen-doped carbon-coated ternary nanoneedle array material described in any one of claims 1 to 3 or the nitrogen-doped carbon-coated ternary nanoneedle array material prepared by the preparation method described in any one of claims 4 to 8 is used as an electrocatalyst.

Citation Information

Patent Citations

  • ZIF-8-based nickel-iron-nitrogen-doped carbon material three-function electrocatalyst, and preparation method and application thereof

    CN112005413A

  • In-situ synthesis composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode and preparation method and application thereof

    CN114121505A

  • Petal-shaped lithium battery negative electrode material rich in oxygen vacancies as well as preparation method and application thereof

    CN116282202A

  • Preparation method of electrolyzed water catalyst applicable to full pH range

    CN117165994A

  • Nitrogen and phosphorus doped cobalt molybdenum oxide / foam cobalt nano array electrode material and preparation method and application thereof

    CN117542669A

Cited By

  • Medium-entropy alloy nitrogen-carbon composite material as well as preparation method and application thereof

    CN122446237A